2022
DOI: 10.3389/fpls.2022.883847
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Transformation and Gene Editing of the B104 Public Maize Inbred by Improved Tissue Culture and Use of Morphogenic Regulators

Abstract: Plant transformation is a bottleneck for the application of gene editing in plants. In Zea mays (maize), a breakthrough was made using co-transformation of the morphogenic transcription factors BABY BOOM (BBM) and WUSCHEL (WUS) to induce somatic embryogenesis. Together with adapted tissue culture media, this was shown to increase transformation efficiency significantly. However, use of the method has not been reported widely, despite a clear need for increased transformation capacity in academic settings. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 66 publications
(115 reference statements)
2
26
0
Order By: Relevance
“…DRs are activated during plant regeneration, with dramatic responses in different plant species. In recent years, transient or stable overexpression of DRs, such as BBM, WUS, GRF5, and GRF4-GIF1, have been proved to successfully overcome this bottleneck in many plants’ genetic transformation processes [ 6 , 7 , 8 , 9 , 10 ].…”
Section: The Merits and Limitations Of Traditional Delivery Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DRs are activated during plant regeneration, with dramatic responses in different plant species. In recent years, transient or stable overexpression of DRs, such as BBM, WUS, GRF5, and GRF4-GIF1, have been proved to successfully overcome this bottleneck in many plants’ genetic transformation processes [ 6 , 7 , 8 , 9 , 10 ].…”
Section: The Merits and Limitations Of Traditional Delivery Methodsmentioning
confidence: 99%
“…However, strong genotype dependence and highly technical requirements of these systems limit their broad application [ 4 , 5 ]. In recent years, the utilization of developmental regulators (DRs), which are also referred to as morphogenic regulators (MRs), such as the WUS (WUSCHEL), BBM (BABY BOOM) and GRFs (GROWTH-REGULATING FACTORs), have been proven to overcome genotype dependence in plant regeneration [ 6 , 7 , 8 , 9 , 10 , 11 ], while in many plant species, the delivery of exogenous DNA or RNA is genotype dependent and is the main bottleneck in genetic transformation. Therefore, there is an urgent need to develop new delivery vectors for genome engineering.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we combined the morphogenic regulators ZmBBM and TaGRF4-GIF1 in a single binary vector carrying Cas9 to explore the potential of this combination to enhance transformation efficiency in two maize genetic backgrounds, Hi-II and B104, commonly used by transformation facilities. While Hi-II is a mixed genetic background, which can complicate phenotypic analysis of transgenic plants, B104 is an inbred line related to B73, the first maize genome to be sequenced and assembled (SCHNABLE et al 2009;RAJI et al 2018;AESAERT et al 2022;KANG et al 2022). In combination with a modified QuickCorn protocol (MASTERS et al 2020), we found that this system significantly enhanced the efficiency of transformation in both backgrounds, allowing the efficient generation of transgenic plants within a two-month time frame.…”
Section: Introductionmentioning
confidence: 92%
“…12,13 ), and two public maize lines, FFMM 14 and B104 (ref. 15 ). In addition, the expression of Wus2 alone has been shown to be effective for improving transformation in maize 16 and genome editing in sorghum 17 .…”
Section: Identification Of Promoters That Stimulate Rapid Somatic Emb...mentioning
confidence: 99%
“…https://doi.org/10.1038/s41477-022-01338-0 was further extended to sorghum transformation 10,12 , sorghum genome editing 37 , maize public inbred transformation 14,15,38 and maize genome editing 15,35,36,39 . Recently, Wox5 has also been demonstrated to improve transformation in numerous wheat varieties, with potential application in other cereals such as Triticum monococcum, triticale, rye, barley and maize 19 .…”
Section: Articlementioning
confidence: 99%